Lower limb muscle activation patterns in ice-hockey skating and associations with skating speed - Kaartinen, S.; Venojärvi, M.; Lesch, K. J.; Tikkanen, H.; Vartiainen, P.; Stenroth, L. (Sports Biomechanics, 2021)
In this study, we aimed to describe lower limb kinematic and muscle activation patterns and then to examine the potential associations between those variables and skating speed in highly trained ice-hockey players. Twelve players (age 18.4-22.0 years) performed five maximal 30-metre forward skating sprints. Skating speeds, muscle activities from eight lower limb muscles (gluteus maximus, gluteus medius, adductor magnus, rectus femoris, vastus lateralis, biceps femoris, tibialis anterior and soleus), and sagittal plane joint angles from the hip and knee joint were measured. A lower activity of the gluteus maximus (r = -0.651, p = 0.022, ß = -0.08) and a reduced gluteus maximus to rectus femoris coactivity (r = -0.786, p = 0.002, ß = -3.26) during the recovery phase were found to be associated with faster skating speed. No significant associations were observed between sagittal plane hip and knee kinematics and skating speed. This study provides evidence that muscle activities during the recovery phase of skating may have an important role in skating performance.